2022
DOI: 10.1002/gps.5839
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression in dementia with Lewy bodies: A longitudinal study on clinical symptoms, quality of life and functional impairment

Abstract: Background and Objectives Dementia with Lewy Bodies (DLB) is a heterogeneous disease, with variable signs and symptoms across multiple domains. We aimed to identify associations with rate of change in cognition, everyday functioning (IADL) and quality of life (QoL). Methods We included 121 DLB patients (69 ± 6 yrs, 14%F, MMSE: 25 ± 3) in our prospective cohort (follow‐up 2 ± 1 yrs). We described progression of symptoms and cognitive decline over time. Mixed models were used to investigate whether changes in sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Using this composite score, hallucinations, constipation, depressive symptoms, and higher IADL dependency were related to lower QoL in univariate analyses, but hallucinations were no longer significant in the multivariable model 5 . In a subsequent longitudinal analysis with a larger cohort, declining QoL (rater not specified) correlated with changes in depressive symptoms, but this was not significant after adjustment for multiple comparisons 6 . In the other study including both patient‐ and proxy‐rated QoL, regression analyses were only performed using proxy‐rated scores 1 .…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Using this composite score, hallucinations, constipation, depressive symptoms, and higher IADL dependency were related to lower QoL in univariate analyses, but hallucinations were no longer significant in the multivariable model 5 . In a subsequent longitudinal analysis with a larger cohort, declining QoL (rater not specified) correlated with changes in depressive symptoms, but this was not significant after adjustment for multiple comparisons 6 . In the other study including both patient‐ and proxy‐rated QoL, regression analyses were only performed using proxy‐rated scores 1 .…”
Section: Introductionmentioning
confidence: 87%
“…Three prior studies specifically queried patient-reported QoL in individuals with DLB, one of which was reported in two publications. 1,[4][5][6] In a study of correlates of patient-reported QoL in early DLB (mean Mini-Mental State Examination [MMSE] score 25, range [22][23][24][25][26][27], worse QoL correlated with more depressive symptoms and higher dependency in instrumental activities of daily living (IADLs). 4 In the DEvELOP cohort including individuals with both mild cognitive impairment and dementia (mean MMSE 25 ± 3), analyses of QoL used a weighted Quality of Life in Alzheimer's Disease (QoL-AD) composite score calculated by combining patient-and caregiver-rated QoL-AD scores, weighting the patient-rated score twice as much.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our results also exhibited relevant differences between functional impairment in AD and LBD, with a constant and more pronounced decline in the latter ( 7 ). Current evidence about the impact of specific NPS on activities of daily living (ADL) decline is scarce, especially in those diagnosed with LBD ( 10–12 ). Previous studies on AD have reported an association between apathy, psychotic symptoms, and functional decline, but the reproducibility of these conclusions should be further examined in external samples ( 13 ).…”
Section: Introductionmentioning
confidence: 99%